2011
DOI: 10.2214/ajr.11.6591
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopically Guided Balloon Dilation of Benign Esophageal Strictures: Incidence of Esophageal Rupture and Its Management in 589 Patients

Abstract: The incidence of esophageal rupture after fluoroscopically guided esophageal balloon dilation was 14.7%. Almost all ruptures were type 1 or 2 and were successfully managed conservatively. Only 1.4% of the ruptures were type 3 and required active management. There was no procedure-related mortality in any patient. Therefore, in spite of the high incidence of ruptures, fluoroscopically guided balloon dilation is a safe procedure, particularly if a rupture is identified early and managed appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 25 publications
2
26
1
Order By: Relevance
“…We found that the total rupture rate secondary to balloon dilatation of benign oesophageal strictures in children was 17.1 %, which was similar to the rupture rate of 14.7 % in the general population [3]. The transmural rupture/perforation rate was 6.2 %, which is in the range of previously reported perforations (0.8-13 %) after balloon dilatation in the paediatric population [11,14].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…We found that the total rupture rate secondary to balloon dilatation of benign oesophageal strictures in children was 17.1 %, which was similar to the rupture rate of 14.7 % in the general population [3]. The transmural rupture/perforation rate was 6.2 %, which is in the range of previously reported perforations (0.8-13 %) after balloon dilatation in the paediatric population [11,14].…”
Section: Discussionsupporting
confidence: 79%
“…One of the most serious complications associated with balloon dilatation is oesophageal rupture [2,3]. Early detection and appropriate treatment of ruptures are very important as delayed treatment can cause high morbidity and mortality [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of sessions of endoscopic or fluoroscopic dilatation depends on the severity of the OS and symptoms [5]. The incidence of major complications such as oesophageal rupture has been reported to be as high as 14.7% following fluoroscopic dilation (with only a minority needing active management), whilst in endoscopic dilatation the incidence of oesophageal perforation is 0.1-0.4% [6,7]The aim of this study was to assess the causes of benign oesophageal stricture, its management and how to predict and prevent advanced stricture in young population.…”
Section: Introductionmentioning
confidence: 99%